Ag-induced Efficient Immobilization of Papain on Silica Spheres - 王安明 王华 周成 杜志强 祝社民 沈树宝 (Chinese journal of chemical engineering, 2008)
Complexation and interaction between silver and amino group were applied to induce an efficient immobilization of papain on silica spheres.Tbe silver nanoparticles were deposited on the silica spheres before p apainwas coupled to the silica spheres. The silica spheres with silver nanoparticles were characterized by high resolution transmission electron microscopy （HR-TEM）, Fournier transform infrared spectroscopy （FT-IR）, and UV-Vis scanning spectrometer. FT-IR spectrum was also used to characterize the immobilized and free papain. Effect of some factors on the activities of the immobilized papain was investigated. It was observed that the coupled yield and relative activity of the papain on Ag/SiO2 were 1.17 and 1.86 times of those on the bare SiO2, respectively. At an optimum concentration of silver, theobserved activity of the immobilized papain was 2.1 timesof that on the bare.silica.In addition, the maximum specific activity of papain immobilized on Ag/SiO2 was 819.9 U·mg·^-1, which is slightly lower than that of the free papain, 906.2 U·mg^-1 . Stability of the immobilized papain was also examined. The resuits indicate that the silver nanoparticles successfully induce a fine immobilization of papain.